Accuracy of recording linear erosion using an unmanned aerial vehicle (UAV) - Rebecca Hinsberger; Alpaslan Yörük (PLoS ONE, 2025)
Soil erosion is an ongoing environmental problem. To address this issue, calibrated erosion models are used to forecast areas vulnerable to erosion and to determine appropriate preventive measures. Model calibrations are based on erosion data recorded using different techniques such as photogrammetry from an unmanned aerial vehicle (UAV). In this study, the accuracy of the DJI P4 RTK UAV data was estimated for cropland boundary conditions. Ground heights of tilled and untilled arable land and standing water surfaces were determined using aerial surveys and compared to terrestrial surveys conducted on site. The results revealed that untilled soils can be accurately detected using a UAV, whereas the detection error rates of tilled soils were 2–3 folds higher. Additionally, the width and height of linear erosion tracks were measured and compared using aerial surveys and manual on-site measurements. The erosion width of the linear tracks was accurately recorded using a UAV whereas the erosion depth was underestimated by the digital elevation model (DEM) generated from UAV data.